Ancient Greek Mercenaries (664–250 BCE) - Trundle, Matthew (History compass, 2005)
Greek mercenary service played a major role in the history of the Archaic and Classical ages (700-323 BCE) down to the early Hellenistic age (250 BCE). Mercenary service became more predominant in the Greek world in this period as the poleis (city-states) coalesced into more stable communities and coinage became more prevalent in the eastern Mediterranean. Greeks proved they were effective warriors in the later Archaic age and so found themselves in greater demand by the imperial powers of the east and the tyrants of Sicily in the Classical period. At the same time warfare became more specialized with the appearance of light troops and cavalry, often mercenaries from the periphery of the Greek world, on the battlefields of the Greek mainland. Mercenary service, like other aspects of Greek military life, reflected and influenced social, economic and political developments in the Greek world in the polis period. This article explores current debates about the origins, nature and general circumstance of Greek mercenary service and gives an overview of its history in the period.